Sequence variations of full-length hepatitis B virus genomes in Chinese patients with HBsAg-negative hepatitis B infection. - Fung-Yu Huang (Public Library of Science (PLoS), 2014)
Background The underlying mechanism of HBsAg-negative hepatitis B virus (HBV) infection is notoriously difficult to elucidate because of the extremely low DNA levels which define the condition. We used a highly efficient amplification method to overcome this obstacle and achieved our aim which was to identify specific mutations or sequence variations associated with this entity. Methods A total of 185 sera and 60 liver biopsies from HBsAg-negative, HBV DNA-positive subjects or known chronic hepatitis B (CHB) subjects with HBsAg seroclearance were amplified by rolling circle amplification followed by full-length HBV genome sequencing. Eleven HBsAg-positive CHB subjects were included as controls. The effects of pivotal mutations identified on regulatory regions on promoter activities were analyzed. Results 22 and 11 full-length HBV genomes were amplified from HBsAg-negative and control subjects respectively. HBV genotype C was the dominant strain. A higher mutation frequency was observed in HBsAg-negative subjects than controls, irrespective of genotype. The nucleotide diversity over the entire HBV genome was significantly higher in HBsAg-negative subjects compared with controls (p = 0.008) and compared with 49 reference sequences from CHB patients (p = 0.025). In addition, HBsAg-negative subjects had significantly higher amino acid substitutions in the four viral genes than controls (all p<0.001). Many mutations were uniquely found in HBsAg-negative subjects, including deletions in promoter regions (13.6%), abolishment of pre-S2/S start codon (18.2%), disruption of pre-S2/S mRNA splicing site (4.5%), nucleotide duplications (9.1%), and missense mutations in "α" determinant region, contributing to defects in HBsAg production. Conclusions These data suggest an accumulation of multiple mutations constraining viral transcriptional activities contribute to HBsAg-negativity in HBV infection.